Inovasi Pemecahan Pembelajaran Bahasa Arab di Madrasah Ibtidaiyah - Nurul Makrifah (STAI Syaichona Moh. Cholil Bangkalan, 2020)
Abstract: This study is aimed to describe the challenge and the innovation of Arabic learning in Islamic Elementary school. The method of this research is descriptive qualitative thas is done by observation and liberary research. The result of this research showed that there are many obstacles of the Arabic learning in this global era that need several innovation to be implemented. The capability of Arabic knowledge should be implemented by a teacher of Arabic to grow the Arabic competence for students in Islamic Elementary School. Besides, several strategies and learning models should be appropriate with the psyche of students in Islamic Elementary School.